The eighth agricultural census in egypt 2009-2010.
The area of cereals grown decreased by 3% to 32,300 ha with the areas of both winter and spring barley decreasing in 2009- 2010. Spring barley fell by 5% but remains the most popular cereal crop with 14,000 ha planted across Northern Ireland. It should be noted that these figures reflect the area planted at 1 June and with the adverse weather in 2009-2010some may remain uncropped or have been ensiled instead.